Beneficial Role of Exercise in the Modulation of mdx Muscle Plastic Remodeling and Oxidative Stress - Monica Frinchi; Giuseppe Morici; Giuseppa Mudó; Maria R. Bonsignore; Valentina Di Liberto (MDPI AG, 2021)
Duchenne muscular dystrophy (DMD) is an X-linked recessive progressive lethal disorder caused by the lack of dystrophin, which determines myofibers mechanical instability, oxidative stress, inflammation, and susceptibility to contraction-induced injuries. Unfortunately, at present, there is no efficient therapy for DMD. Beyond several promising gene- and stem cells-based strategies under investigation, physical activity may represent a valid noninvasive therapeutic approach to slow down the progression of the pathology. However, ethical issues, the limited number of studies in humans and the lack of consistency of the investigated training interventions generate loss of consensus regarding their efficacy, leaving exercise prescription still questionable. By an accurate analysis of data about the effects of different protocol of exercise on muscles of mdx mice, the most widely-used pre-clinical model for DMD research, we found that low intensity exercise, especially in the form of low speed treadmill running, likely represents the most suitable exercise modality associated to beneficial effects on mdx muscle. This protocol of training reduces muscle oxidative stress, inflammation, and fibrosis process, and enhances muscle functionality, muscle regeneration, and hypertrophy. These conclusions can guide the design of appropriate studies on human, thereby providing new insights to translational therapeutic application of exercise to DMD patients.